WANPRESTASI PENYEWA DALAM PERJANJIAN SEWA MENYEWA RUKO PADA PEMILIK DI DESA SOSOK II KECAMATAN TAYAN HULU KABUPATEN SANGGAU - DESY S. MELIALA NIM. A1011181024 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac The rental agreement for renting a shop house (shop house (ruko)) on Jalan Raya Gambar 2 Dusun Moling in Tayan Hulu District, Sanggau Regency has a period of 1 (one) year, starting from the date the lease agreement was signed verbally, accompanied by an upfront payment as a sign of completion of 50% of the total rental fee determined by the owner of the shop house (house shop (ruko)). Of the 2 (two) shop houses (shophouses (ruko)) all of them have been rented and occupied by their respective tenants, to run various businesses. Like someone who rents to open a restaurant and coffee shop (cafe). In accordance with the agreement regarding the rental period (rumah toko (ruko), where the shop house (ruko) is rented for 1 (one) year at a rental price of Rp.24,000,000,- (twenty four million rupiah) per year. the remaining 50% or Rp.12,000,000,- (twelve million rupiahs) can be paid in installments with a note that the remaining payment must be paid in full at least 3 (three) months before the rental period ends. the tenant is late in paying the remaining rent in the rental of the shop house (ruko), until the rental period of the shop house (ruko) the tenant has not paid the remaining rent for the shop house (ruko) which ends due to the current covid-19 pandemic, 50% can be paid in installments with a note that the remaining payment must be paid in full at least 3 (three) months before the rental period ends, but so far it has not been paid for by the tenants of the shophouse (ruko).The problem in this research is: